Релейная защита и автоматика электрических систем: сб. науч. тр. / Риж. политехн. ин-т - Орехов Леонид Александрович (РПИ, 1988)
Экземпляры: КХ (20080805) / Инвентарный номер: 927507 / Цена: 1.10 / Сис.шифр: 31.27 / Авт.знак: Р 36 / ГРНТИ: 45 / ББК: 31.27-053